Determinants of civil service in EU countries: Analysis using multivariate methods - Martina Halásková; Václav Friedrich; Ivana Čermáková (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2021)
Systems of civil service reflect specific needs, traditions and institutional fundamentals of every state. The paper provides an outline of the European context of civil service, characteristics of basic features of civil service in EU countries, and evaluation of selected determinants of civil service from the perspectives of human resources, finances, and performance. Factor analysis, hierarchical cluster analysis and analysis of variance are applied in the research to evaluate the period 2012-2019 in the 27 EU countries. Factor analysis was used to assign the selected determinants of civil service in the EU countries with the three factors created (performance of civil service, financial dimension of civil service, employees of civil service). The evaluation of the factors of the civil service in the EU countries using hierarchical cluster analysis has resulted in five clusters of countries with similar characteristic features of civil service. The strongest similarity is seen in the clusters of the EU countries in performance of civil service and employees of civil service. The results of the EU countries also indicate similarity of average values of civil service factors. Analysis of civil service determinants has proved that in the majority of countries placed in the same cluster according to the similarity of civil service, a relation exists in terms of the same tradition of the civil service but also in terms of the geographical viewpoint. Despite differences, similar tendencies can be observed related to increased flexibility, performance and modernisation of civil service systems.
Keywords: H10; H83; C38; 330; Civil service; Civil servants; Determinants of civil service; EU countries; Factor analysis; Hierarchical cluster analysis